Antibiotic prescribing of village doctors for children under 15 years with upper respiratory tract infections in rural China: A qualitative study - Zhang, Zhixia (Medicine (Baltimore), 2016)
The aim of this study was to explore the knowledge, attitudes, and practices of village doctors regarding the prescribing of antibiotics for children under 15 years with upper respiratory tract infections (URTIs) in rural China. Twelve focus group discussions (FGDs) were conducted in Xianning, a prefecture-level city in rural China, during December 2014. We conducted 6 FGDs with 35 village doctors, 3 with 13 primary caregivers (11 parents), and 3 with 17 directors of township hospitals, county-level health bureaus, county-level Centers for Disease Control and Prevention, or county-level Chinese Food and Drug Administration offices. Audio records of the interviews were transcribed verbatim and analyzed using the thematic analysis approach. Participants believed that unnecessary antibiotic prescribing for children under 15 years with The occurrence of URTIs was a problem in village clinics in rural China. The discussions revealed that most of the village doctors had inadequate knowledge and misconceptions about antibiotic use, which was an important factor in the unnecessary prescribing. Village doctors and directors reported that the doctors’ fear of complications, the primary caregivers’ pressure for antibiotic treatment, and the financial considerations of patient retention were the main factors influencing the decision to prescribe antibiotics. Most of the primary caregivers insisted on antibiotics, even when the village doctors were reluctant to prescribe them, and they preferred to go to see those village doctors who prescribed antibiotics. The interviewees also gave their opinions on what would be the most effective measures for optimizing antibiotic prescriptions; these included educational/training campaigns, strict regulations on antibiotic prescription, and improved supervision. Findings emphasized the need to improve the dissemination of information and training/education, and implement legislation on the rational use of antibiotics. And it also provided helpful information to guide the design of more effective interventions to promote prudent antibiotic use and good antimicrobial stewardship.